An investigation into the determinants of the South African unemployment rate, 1970-2002 - Schoeman, Christie; Blaauw, Derick; Pretorius, Anmar (University of the Free State, 2008)
From 1970 to 1977 unemployment in South Africa oscillated around a near-constant mean. Since 1983 unemployment has shown a definite upward trend defying the existence of a long-run natural rate. South African unemployment data exhibits signs of hysteresis, suggesting that long-run unemployment is endogenously determined. Empirical results confirm that the total fixed capital stock, interest rate and degree of unionisation of the labour force are important factors in explaining the unemployment rate in South Africa. This implies that long-run equilibrium unemployment in South Africa is endogenously determined by economic as well as institutional factors.

Die Suid-Afrikaanse werkloosheidskoers het van 1970 tot 1977 rondom ’n bynakonstante gemiddelde beweeg. Sedert 1983 is daar ’n duidelike opwaartse neiging wat die bestaan van ’n langtermyn natuurlike werkloosheidskoers weerspreek. Histerese blyk teenwoordig te wees in Suid-Afrikaanse werkloosheidsyfers wat dui op die endogene aard van langtermyn werkloosheid. Empiriese ontleding bevestig dat totale vaste kapitaalvoorraad, rentekoerse en die invloed van vakbondbedrywighede in die arbeidsmag belangrike bydraers tot Suid-Afrikaanse werkloosheid is. Die langtermyn ewewigsvlak van werkloosheid word endogeen bepaal deur ekonomiese sowel as institusionele faktore.
Keywords: Unemployment; South African unemployment; Labour force; South African economy